(Re) Appropriation of knowledge. Actors, territories, processes, issues - (:unkn) unknown (My University, 2021)
At the crossroads of fields and disciplines, this collective book proposes a new reflection on the concept of appropriation or reappropriation of knowledge and know-how based on specific situations. It focuses the analyses on the actors' point of view, their commitments, their aims and objectives, and by taking an interest in the power of initiative and the strategies they deploy in the production and use of knowledge.Based on case studies, the book provides a global approach to the issue thanks to the wide range of fields studied: Africa - Sub-Saharan Africa, Ivory Coast, Morocco; America - Mexico, Haiti; Asia - India, China, Iran; Europe, France. It brings together the reflections of four anthropologists, six historians, two sociologists, a geographer and a specialist in literary history.Without fixing the definition of these (re)appropriation processes, the aim is to consider them from a methodological and heuristic point of view. Beyond the notions of "cultural transfer" or "acculturation" already worked on or analysis of knowledge distribution or circulation adopted or rejected in certain regions, the book gives focuses instead on the agentivity of the actors in these processes of integration of knowledge or know-how considered as exogenous or rediscovered after long periods of oblivion.The proposed case studies could feed theoretical reflections, serve as a basis for regional studies, or allow comparative approaches.
Keywords: African Research